Truss optimization under complex constraints and random loading - Norkus, Arnoldas; Karkauskas, Romanas (Journal of Civil Engineering and Management, 2004)
An actual design of light‐weight structures must evaluate strength, stiffness and stability constraints as well as the nature of external loading. A designed structure must satisfy optimality and safety criterions per prescribed maintenance period. One faces the known difficulties when trying to implement several from the above‐mentioned requirements into optimization problem for further successful numerical realisation. A method to formulate the optimization problem, incorporating all above described criterions, the mathematical model and algorithm to solve it numerically, taking into account the stochastic nature of external loading, are presented for elastic‐plastic truss‐type structure.First Published Online: 14 Oct 2010